Metabolomics reveals increased toxicity in earthworms (Eisenia fetida) of the transformation product methyl-triclosan - J.D. Gillis; G.W. Price; S.O. Prasher; Behnam Asgari Lajayer (Ecotoxicology and Environmental Safety, 2025)
The effects of triclosan (TCS) and its transformation product methyl-triclosan (MTCS) on the earthworm Eisenia fetida were investigated using Gas chromatography–mass spectrometry (GC-MS) metabolomics. Earthworms were exposed to 0, 0.25, 1, 4, 16, and 64 µg g−1 of either TCS or MTCS for 14 days in commercial worm bedding. Only MTCS exposure caused any effects on the earthworm metabolites targeted in this study. Succinic acid was elevated relative to the control at concentrations ≥ 0.25 µg g−1 and glucose was elevated at 1 µg g−1. Earthworms exposed to 1 µg g−1 MTCS had the greatest separation from the control using Principal Components Analysis (PCA), while 0.25 and 1 µg g−1 had the largest separation in Discriminant Analysis (DA). Essential amino acids valine, leucine, serine, and phenylalanine had large, standardized coefficients for PCA and DA reflecting their contribution to separation, suggesting that essential amino acid homeostasis was perturbed by MTCS. Malic acid, succinic acid, margaric acid, and glucose were highly correlated (p < 0.01) with Canonical 1 and PC 2, while maltose was correlated with Canonical 2 and PC 7, indicating a strong relationship between these metabolites and the multivariate separation expressed in the canonical variables. Disruption of succinate metabolism by membrane destabilization in mitochondria was hypothesized as a possible mode of action for MTCS.